2014
DOI: 10.1021/jp509516x
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of 2-Chloroethyl Ethyl Sulfide on Silica: Binding Mechanism and Energy of a Bifunctional Hydrogen-Bond Acceptor at the Gas–Surface Interface

Abstract: This work investigates the fundamental nature of sulfur mustard surface adsorption by characterizing interfacial hydrogen bonding and other intermolecular forces for the surrogate molecule (simulant) 2-chloroethyl ethyl sulfide (2-CEES). Adsorption at the surface of amorphous silica is the focus of this work because of silica’s low chemical reactivity, well-known properties, and abundance in the environment. 2-CEES has two polar functional groups, the chloro and thioether moieties, available to accept hydrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 33 publications
(65 reference statements)
5
51
0
Order By: Relevance
“…1a). Based on similar results, previous infrared studies have also reported the presence of hydrogen bonding between other molecules and the SiO 2 surface 20,33,34. A detailed peak assignment for limonene adsorbed on hydroxylated SiO 2 is provided in the ESI (Table S1†) and shows that the vibrational frequencies are close to that for limonene in the gas and liquid phases.…”
Section: Resultssupporting
confidence: 73%
“…1a). Based on similar results, previous infrared studies have also reported the presence of hydrogen bonding between other molecules and the SiO 2 surface 20,33,34. A detailed peak assignment for limonene adsorbed on hydroxylated SiO 2 is provided in the ESI (Table S1†) and shows that the vibrational frequencies are close to that for limonene in the gas and liquid phases.…”
Section: Resultssupporting
confidence: 73%
“…The defective UiO-66 SBU used in this work is based on that described by Ling and Slater, and exhibits a hydroxide ligand saturating one of the undercoordinated Zr atoms, with the nerve agent bound on the other undercoordinated Zr atom (Figure a). This SBU is used to simulate future ultrahigh-vacuum (UHV) experiments in which a customary thermal treatment of the surface removes physisorbed water and other adsorbates prior to exposure to the nerve agent. , In UHV conditions, the Zr–OH catalyst in Figure a can also be generated via dissociation of a coordinated aqua ligand on the defective SBU, as shown in the figure. The water dissociation reaction is exothermic by 19.0 kJ/mol and proceeds over a low barrier of 30.0 kJ/mol.…”
Section: Resultsmentioning
confidence: 99%
“…A final note in our discussion of the general base hydrolysis mechanism is that under ambient conditions, the presence of atmospheric water will likely facilitate this pathway with respect to the one not mediated by water described before. On the other hand, the dry mechanism will likely be operational in fundamental gas-surface experiments under ultrahigh vacuum, where customary thermal treatment cleans the surface of the catalyst prior to exposure to nerve agents or simulants. , …”
Section: Resultsmentioning
confidence: 99%
“…Among several methods to remove toxic chemicals, adsorptive removal is signicant, due to its simple operation and cost effectiveness. 34,[41][42][43][44][45][46][47][48][49] There are few reports where MOFs are used for this purpose, but the mechanism of these types of adsorption processes is still ambiguous. In the present work, we have used Zr-based MOFs (NU-1000 and UiO-67) for the efficient adsorption and removal of CWA simulants, (or namely) 2-CEES and DMMP from the aqueous medium.…”
Section: Introductionmentioning
confidence: 99%